Clients of the Pretoria Cochlear Implant Programme : characteristics and perceived outcomes of children and their families - Kritzinger, Alta M. (Aletta Margaretha) (University of Pretoria, 2013)
Dissertation (M (Communication Pathology))--University of Pretoria, 2006.